2018
DOI: 10.3389/fimmu.2018.01414
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Signaling Is Frequently Downregulated in Melanoma

Abstract: Immune checkpoint inhibitors that block the programmed cell death protein 1/PD-L1 pathway have significantly improved the survival of patients with advanced melanoma. Immunotherapies are only effective in 15–40% of melanoma patients and resistance is associated with defects in antigen presentation and interferon signaling pathways. In this study, we examined interferon-γ (IFNγ) responses in a large panel of immune checkpoint inhibitor-naïve melanoma cells with defined genetic drivers; BRAF-mutant (n = 11), NRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 38 publications
(49 reference statements)
3
20
0
Order By: Relevance
“…Rodig et al also found that melanoma MHC-II but not MHC-I expression by immunohistochemistry (IHC) was predictive of week-13 response to anti-PD-1 monotherapy in the CheckMate 064 trial [ 18 ]. We now confirm that expression of MHC-I and MHC-II proteins on tumor cell surface is highly correlated, as was previously observed at both the transcript and protein levels [ 19 ]. While it is difficult to directly compare flow cytometric- and immunohistochemistry-based estimates of MHC expression, we found that IHC-defined thresholds associated with immunotherapy response, 30% for MHC-I [ 18 ] and 1% [ 18 ] or 5% for MHC-II [ 20 ], identified only 43% of MHC-I low tumors in our study and 50% or 83% of MHC-II low tumors, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Rodig et al also found that melanoma MHC-II but not MHC-I expression by immunohistochemistry (IHC) was predictive of week-13 response to anti-PD-1 monotherapy in the CheckMate 064 trial [ 18 ]. We now confirm that expression of MHC-I and MHC-II proteins on tumor cell surface is highly correlated, as was previously observed at both the transcript and protein levels [ 19 ]. While it is difficult to directly compare flow cytometric- and immunohistochemistry-based estimates of MHC expression, we found that IHC-defined thresholds associated with immunotherapy response, 30% for MHC-I [ 18 ] and 1% [ 18 ] or 5% for MHC-II [ 20 ], identified only 43% of MHC-I low tumors in our study and 50% or 83% of MHC-II low tumors, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has shown that many melanoma cells and cell lines have variable defects in interferon signaling pathways (74)(75)(76), which was also observed in the melanoma cell line that we used as feeder cells for this study (77,78). Moreover, compared to infected BMDCs, we observed in MVAinfected S91 feeder cells a severely limited cytokine/chemokine response with a complete lack of type I and II interferons ( Supplementary Figure 7).…”
Section: Discussionsupporting
confidence: 68%
“…Interestingly, we observed significant downregulation of the IRF transcription factor family members (IRF1, IRF2, IRF5, IRF8) corresponding to attenuated interferon signaling in TRIM28 HIGH melanomas, probably as a consequence of low immune cell infiltration. Recently, Alavi S. et al [ 50 ] have reported that downregulation of interferon signaling occurred in almost 70% of immunotherapy-naïve melanomas, although they did not link this phenomenon with TRIM28 expression. As TRIM28 is a well-known transcriptional co-repressor, we suggest that low IRF1 , IRF2 , IRF5 , and IRF8 expression (in the absence of stimulating signaling) result from TRIM28-mediated epigenetic modifications within the IRF promoters.…”
Section: Discussionmentioning
confidence: 99%